2021
DOI: 10.2217/fon-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Complications After Neoadjuvant Chemotherapy or Chemoradiotherapy for Esophageal Cancer: A Meta-Analysis

Abstract: Objectives: To identify the effective approach between neoadjuvant chemotherapy (NCT) and chemoradiotherapy (NCRT) by comparing patient survival and complications. Methods: A systematic literature search of articles published between January 1980 and October 2020 was conducted. Data were extracted and analyzed with STATA 12.0. Results: Five randomized trials and 15 retrospective studies, including 4529 patients (NCT: 2035; NCRT: 2494), were enrolled. Compared with NCT, NCRT provided a higher 3-year survival be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 43 publications
6
19
0
Order By: Relevance
“…Kamarajah et al analyzed the National Cancer Database (2006-2015) including 2,367 with ESCC (nCRT 2,155 and nCT 212) and found that for ESCC, nCRT followed by surgery had advantage in pCR rate (50.9% versus 30.4%; p < 0.001), margin-negative resections (92.8% versus 82.4%, p < 0.001), and a statistically significant overall survival benefit (hazard ratio (HR) 0.78, 0.62 to 0.97) (23). A recent meta-analysis including 4,529 patients (nCT 2,035 and nCRT 2,494) showed that compared with nCT, nCRT could provide a higher 3-year survival benefit, higher R0 resection, and pCR rates, but no increase in 5-year survival (24). Zhang et al conducted a propensity score-matched study from the National Cancer Center to compare the long-term results between nCRT and nCT and found that significantly higher pCR rates in the nCRT group did not lead to a longer survival (25).…”
Section: Discussionmentioning
confidence: 99%
“…Kamarajah et al analyzed the National Cancer Database (2006-2015) including 2,367 with ESCC (nCRT 2,155 and nCT 212) and found that for ESCC, nCRT followed by surgery had advantage in pCR rate (50.9% versus 30.4%; p < 0.001), margin-negative resections (92.8% versus 82.4%, p < 0.001), and a statistically significant overall survival benefit (hazard ratio (HR) 0.78, 0.62 to 0.97) (23). A recent meta-analysis including 4,529 patients (nCT 2,035 and nCRT 2,494) showed that compared with nCT, nCRT could provide a higher 3-year survival benefit, higher R0 resection, and pCR rates, but no increase in 5-year survival (24). Zhang et al conducted a propensity score-matched study from the National Cancer Center to compare the long-term results between nCRT and nCT and found that significantly higher pCR rates in the nCRT group did not lead to a longer survival (25).…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis of studies involving 4529 patients with esophageal cancer, compared with NCT, nCRT provided a higher pCR rate, higher R0 surgical resection rate, and lower local recurrence and distant metastasis rates but no increase in 5-year survival. 67 Based on trials involving 4563 patients with esophageal cancer, a network meta-analysis observed no differences between NCT and nCRT regarding OS and disease-free survival. 68 Due to the limitations of available data, we could not explore the differences in results between neoadjuvant immunotherapy combined with chemotherapy and neoadjuvant immunotherapy combined with CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Kamarajah et al reported that compared to nCT, overall survival benefit was evident for nCRT (HR 0.78, 0.62 to 0.97), and recommended nCRT followed by surgery for ESCC (6). A meta-analysis including 4,529 patients (nCT: 2,035; nCRT: 2,494) found that compared to the nCT group, deaths caused by tumor progression or recurrence were significantly less in the nCRT group than in the nCT group; however, there was not an increase in 5-year survival (7). Optimal neoadjuvant treatment strategy for locally advanced ESCC is still controversial and not promising.…”
Section: Introductionmentioning
confidence: 99%